A common SNP in the UNG gene decreases ovarian cancer risk in BRCA2 mutation carriers - Juan Miguel Baquero; Carlos Benítez‐Buelga; Victoria Fernández; Miguel Urioste; Jose Luis García‐Giménez; Rosario Perona; the CIMBA Consortium; Javier Benítez; Ana Osorio (Molecular Oncology)
Single nucleotide polymorphisms (SNPs) in DNA glycosylase genes involved in the base excision repair (BER) pathway can modify breast and ovarian cancer risk in BRCA1 and BRCA2 mutation carriers. We previously found that SNP rs34259 in the uracil‐DNA glycosylase gene (UNG) might decrease ovarian cancer risk in BRCA2 mutation carriers. In the present study, we validated this finding in a larger series of familial breast and ovarian cancer patients to gain insights into how this UNG variant exerts its protective effect. We found that rs34259 is associated with significant UNG downregulation and with lower levels of DNA damage at telomeres. In addition, we found that this SNP is associated with significantly lower oxidative stress susceptibility and lower uracil accumulation at telomeres in BRCA2 mutation carriers. Our findings help to explain the association of this variant with a lower cancer risk in BRCA2 mutation carriers and highlight the importance of genetic changes in BER pathway genes as modifiers of cancer susceptibility for BRCA1 and BRCA2 mutation carriers.